Developing a Local Wisdom-Based E-Book to Instill Moral Values in Kindergarten Children - Rafita, Masri; Puspa Juwita, Rani (Journal of Islamic Education Students (JIES), 2025)
The lack of contextually relevant digital learning media rooted in local culture has contributed to low levels of interest and engagement among kindergarten children in learning moral values. This study aims to develop a local wisdom-based e-book from Aceh as an instructional medium to foster moral education in early childhood. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) combined with a descriptive quantitative method. The sample consisted of 18 children aged 5ÔÇô6 years. Data were collected through expert validation (media and content) and observations of child engagement during the e-book trial phase. The results indicated that the e-book was highly feasible, with media expert validation scores reaching 80%, content expert validation scores at 90%, and product trial results with children ranging from 92% to 100%. These findings demonstrate that digital media grounded in local wisdom can effectively enhance young childrenÔÇÖs engagement and understanding of moral values.